2014
DOI: 10.1021/ar5001764
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Atomic-Level Mechanisms for Gas-Phase X + CH3Y SN2 Reactions by Combined Experiments and Simulations

Abstract: For the traditional model of gas-phase X(-) + CH3Y SN2 reactions, C3v ion-dipole pre- and postreaction complexes X(-)---CH3Y and XCH3---Y(-), separated by a central barrier, are formed. Statistical intramolecular dynamics are assumed for these complexes, so that their unimolecular rate constants are given by RRKM theory. Both previous simulations and experiments have shown that the dynamics of these complexes are not statistical and of interest is how these nonstatistical dynamics affect the SN2 rate constant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
156
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 44 publications
9
156
0
4
Order By: Relevance
“…Similar profiles were observed in related cases modeled by DFT, as in the bimolecular S N 2 reaction X − + CH 3 Y → XCH 3 + Y − . 71 Thus, the first step consists of the interaction of the Pt 2 (II,II) precursor acting as a nucleophile with the haloalkane. The formed adduct results from the stabilizing interaction of the Pt 2 -centered highest occupied molecular orbital of the dinuclear complex with the electrophillic C atom of the halogenated substrate.…”
Section: Mechanismmentioning
confidence: 99%
“…Similar profiles were observed in related cases modeled by DFT, as in the bimolecular S N 2 reaction X − + CH 3 Y → XCH 3 + Y − . 71 Thus, the first step consists of the interaction of the Pt 2 (II,II) precursor acting as a nucleophile with the haloalkane. The formed adduct results from the stabilizing interaction of the Pt 2 -centered highest occupied molecular orbital of the dinuclear complex with the electrophillic C atom of the halogenated substrate.…”
Section: Mechanismmentioning
confidence: 99%
“…However, recent theoretical and experimental investigations showed that the dynamics is not so simple. [3][4][5][6][7][8][9][10][11][12] Besides the direct rebound mechanism described above, direct stripping (X − approaches the side of CH 3 Y and strips off CH 3 ), front-side attack (direct replacement of Y − without inversion), and indirect mechanisms (complex formations, roundabout, 6 and barrier recrossing) can occur. Moreover, our recent reaction dynamics computations revealed a new double-inversion mechanism for the F − + CH 3 Cl S N 2 reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high barrier of the former, the S N 2 reactions are known to proceed via Walden inversion at low collision energies (E coll ) and the front-side attack pathway may open at higher E coll . Note that one may distinguish between direct rebound and stripping, as well as indirect (iondipole and/or hydrogen-bonded complex formation, roundabout and barrier recrossing) mechanisms 14 , but in the present study we consider these as variants of the back-side attack inversion mechanism.…”
mentioning
confidence: 99%